O pensamento filosófico de Viktor Emil Frankl: Mundo, homem e Deus - Pereira, Ivo Studart (2017)
Our motivation to write this thesis derives from the need to present the relevance of Viktor Emil Frankl's opus within contemporary philosophy, given a current deficient research status in this field. Thus, this research aims to contribute in overcoming an academic gap that does not do justice to the importance of the Viennese thinker's legacy. In order to accomplish that, we were guided by the hypothesis that there is an authentic Franklian philosophical work and that it can be systematically conceptualized under three major areas of research: 1) world view, 2) concept of man and 3) the question of God. We seek to demonstrate that Frankl presents clear points in each of the aforementioned philosophical domains, forming a systematic conceptual universe. In the first area, our sub-hypothesis is that the category "meaning" constitutes the conceptual key to define the contours of Frankl’s Weltanschauung, serving as a foundation for what we construe as a true axiological foundation of the world. The second macro-theme involving our investigation concerns the "metaclinical theory" of human nature that the founder of logotherapy has built in order to substantiate his psychotherapeutic approach. Our sub-hypothesis here is that there is a Franklian philosophical anthropology, which must be understood from the category "spirit" as a "spiritual dimension". The third domain within our investigation assumes the sub-hypothesis that a peculiar form of philosophical theology underlies Frankl’s thought, stemming from his interpretation of the moral conscience (Gewissen) as the “voice of transcendence”, legitimating the phenomenon of responsibility. The key category here is that of "supermeaning" - the meaning that dimensionally refers to the Absolute, inspiring what Frankl called "basic trust in being," as a peculiar form of faith that would be common to the human race.